The Multifaceted Roles of NRF2 in Cancer: Friend or Foe? - Christophe Glorieux; Cinthya Enríquez; Constanza González; Gabriela Aguirre-Martínez; Pedro Buc Calderon (MDPI AG, 2024)
Physiological concentrations of reactive oxygen species (ROS) play vital roles in various normal cellular processes, whereas excessive ROS generation is central to disease pathogenesis. The nuclear factor erythroid 2-related factor 2 (NRF2) is a critical transcription factor that regulates the cellular antioxidant systems in response to oxidative stress by governing the expression of genes encoding antioxidant enzymes that shield cells from diverse oxidative alterations. NRF2 and its negative regulator Kelch-like ECH-associated protein 1 (KEAP1) have been the focus of numerous investigations in elucidating whether NRF2 suppresses tumor promotion or conversely exerts pro-oncogenic effects. NRF2 has been found to participate in various pathological processes, including dysregulated cell proliferation, metabolic remodeling, and resistance to apoptosis. Herein, this review article will examine the intriguing role of phase separation in activating the NRF2 transcriptional activity and explore the NRF2 dual impacts on tumor immunology, cancer stem cells, metastasis, and long non-coding RNAs (LncRNAs). Taken together, this review aims to discuss the NRF2 multifaceted roles in both cancer prevention and promotion while also addressing the advantages, disadvantages, and limitations associated with modulating NRF2 therapeutically in cancer treatment.